Sagittal Balance in Adult Idiopathic Scoliosis. Issue 2 (March 2020) - Nolte, Michael T.; Louie, Philip K.; Harada, Garrett K.; Khan, Jannat M.; Ferguson, Joseph; Dewald, Christopher J.; An, Howard S.
Abstract : Study Design: A narrative review article study. Objective: The objective of this study was to highlight guiding principles and challenges faced with addressing sagittal alignment in patients with adult idiopathic scoliosis (AIS) and to discuss effective surgical strategies based upon our clinical experience. Summary of Background Data: Previous research and guidelines for the treatment of AIS have focused on the correction of spinal deformity in the coronal and axial planes. Failure to address sagittal deformity has been associated with numerous adverse clinical outcomes. Methods: This is a review of the current body of literature and a description of the rod derotation surgical technique for correction in the sagittal plane. Results: Several studies have offered general goals for postoperative radiographic measures in the sagittal plane for patients with AIS. However, these guidelines are evolving as diagnostic and therapeutic modalities continue to improve. The rod derotation surgical technique through differential metal rods is one method to potentially address sagittal balance in AIS. Conclusions: Alignment in the sagittal plane is a unique challenge facing surgeons for patients with AIS. Further research with an assessment of functional outcomes and longer follow-up is needed to more precisely guide treatment principles. Level of Evidence: Level IV.